Kontribusi Satuan Pengamanan dan Pedagang Kantin dalam Membangun Karakter Antikorupsi Generasi Muda di Sekolah - Septiano Andreas Hendrata (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This article discusses the crucial role of security guards and canteen vendors in building anti-corruption character among the youth in educational environments. In an era where corruption poses a serious problem across various sectors, character education based on anti-corruption values becomes imperative. Security guards, as the frontline protectors in schools, serve not only to maintain security but also to exemplify good behavior for students. Meanwhile, canteen vendors can influence students' attitudes toward integrity and transparency through honest business practices. Through the collaboration of both parties, it is hoped that a conducive school environment for instilling anti-corruption values can be created. The conclusion of this article is that the active involvement of security guards and canteen vendors significantly contributes to shaping students' anti-corruption character. Recommendations include the need for training and socialization regarding anti-corruption values for both parties to enhance their roles in character education.